Trend and Outcomes of Video Laryngoscope Use Across PICUs*. Issue 8 (August 2017) - Grunwell, Jocelyn R.; Kamat, Pradip P.; Miksa, Michael; Krishna, Ashwin; Walson, Karen; Simon, Dennis; Krawiec, Conrad; Breuer, Ryan; Lee, Jan Hau; Gradidge, Eleanor; Tarquinio, Keiko; Shenoi, Asha; et al.
Abstract : Objective: Video (indirect) laryngoscopy is used as a primary tracheal intubation device for difficult airways in emergency departments and in adult ICUs. The use and outcomes of video laryngoscopy compared with direct laryngoscopy has not been quantified in PICUs or cardiac ICUs. Design: Retrospective review of prospectively collected observational data from a multicenter tracheal intubation database (National Emergency Airway Registry for Children) from July 2010 to June 2015. Setting: Thirty-six PICUs/cardiac ICUs across the United States, Canada, Japan, New Zealand, and Singapore. Patients: Any patient admitted to a PICU or a pediatric cardiac ICU and undergoing tracheal intubation. Interventions: Use of direct laryngoscopy versus video laryngoscopy for tracheal intubation. Measurements and Main Results: There were 8, 875 tracheal intubations reported in the National Emergency Airway Registry for Children database, including 7, 947 (89.5%) tracheal intubations performed using direct laryngoscopy and 928 (10.5%) tracheal intubations performed using video laryngoscopy. Wide variability in video laryngoscopy use exists across PICUs (median, 2.6%; range, 0–55%). Video laryngoscopy was more often used in older children ( p < 0.001), in children with history of a difficult airway ( p = 0.01), in children intubated for ventilatory failure ( p < 0.001), and to facilitate the completion of an elective procedure ( p = 0.048). After adjusting for patient-level covariates, a secular trend, and site-level variance, the use of video laryngoscopy significantly increased over a 5-year period compared with fiscal year 2011 (odds ratio, 6.7; 95% CI, 1.7–26.8 for fiscal year 2014 and odds ratio, 11.2; 95% CI, 3.2–38.9 for fiscal year 2015). The use of video laryngoscopy was independently associated with a lower occurrence of tracheal intubation adverse events (adjusted odds ratio, 0.57; 95% CI, 0.42–0.77; p < 0.001) but not with a lower occurrence of severe tracheal intubation adverse events (adjusted odds ratio, 0.86; 95% CI, 0.56–1.32; p = 0.49) or fewer multiple attempts at endotracheal intubation (adjusted odds ratio, 0.93; 95% CI, 0.71–1.22; p = 0.59). Conclusions: Using National Emergency Airway Registry for Children data, we described patient-centered adverse outcomes associated with video laryngoscopy compared with direct laryngoscopy for tracheal intubation in the largest reported international cohort of children to date. Data from this study may be used to design sufficiently powered prospective studies comparing patient-centered outcomes for video laryngoscopy versus direct laryngoscopy during endotracheal intubation. Abstract : Supplemental Digital Content is available in the text.